2022
DOI: 10.5713/ab.21.0264
|View full text |Cite
|
Sign up to set email alerts
|

Cooked broiler meat quality affected by different Mediterranean medicinal plants in the diet

Abstract: Objectives: This study was conducted to investigate the effects of adding oregano (Origanum syriacum L.) and germander (Teucrium polium L.) to poultry diets individually and/or in combination : 1) on cooked chicken meat quality and storage stability, 2) to compare this effect with those of the synthetic antioxidant butylated hydroxyanisole (BHA) and with the normal basic diet (Control: without supplements).Methods: Broilers (140 birds) were raised for 21 days and then equally divided into five different treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, its worst than Rosa Polandia chickens, which is 0.860-0.111g/100g [18]. Additionally, the size of the ventriculus in KUB chickens is greater than in Hisex Brown chickens, both in the cage system (1.556g/100g) and the floor system (1.742g/100g) [16].…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, its worst than Rosa Polandia chickens, which is 0.860-0.111g/100g [18]. Additionally, the size of the ventriculus in KUB chickens is greater than in Hisex Brown chickens, both in the cage system (1.556g/100g) and the floor system (1.742g/100g) [16].…”
Section: Resultsmentioning
confidence: 97%
“…It cause the form of the feed is the same, crumble so it does not affect the difference in ventriculus. The cortisol hormone appears in conditions of long-term stress and could cause an increase in blood pressure [16]. The size of the proventriculus in KUB chickens is equivalent to 25week-old Hyline chickens, which is 0.325-0.368g/100g [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To prevent the problem of lipid peroxidation, synthetic antioxidants have been applied, but their residues in the meat carcasses have raised health concerns due to their carcinogenic properties [16,17]. Several studies have suggested the inclusion of natural antioxidants in chicken diets as a solution to the problem of lipid peroxidation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%